2021
DOI: 10.23939/chcht15.04.457
|View full text |Cite
|
Sign up to set email alerts
|

Superhigh Adsorption of Cadmium(II) Ions onto Surface Modified Nano Zerovalent Iron Composite (CNS-nZVI): Characterization, Adsorption Kinetics and Isotherm Studies

Abstract: The efficiency of surface modified nanoscale zerovalent iron (nZVI) composite by cashew nut shell (CNS) was tested for the removal of cadmium ions from the aqueous solutions. 2 g/l CNS-nZVI was efficient for 98% removal. The adsorption capacity was 35.58 mg/g. The Freundlich isotherm (R2 = 0.9769) and the pseudo-second order adsorption kinetics data fitted well. This proved CNS-nZVI has a high removal efficiency for Cd(II) from aqueous solutions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 28 publications
0
6
0
Order By: Relevance
“…As there was a rise in the sorbent dosage of Fe 3 O 4 @SiO 2 -NH 2 nanoparticles, the percentage of removal increased, but the q e decreased. From this trend, it can be clearly understood that a rise in the number of active sites favors sorption [57]. From the results depicted in Figure 4b, it was observed that 2.0 g/L seems to give ample interchangeable binding sites for the removal of cadmium ions.…”
Section: Impact Of Dosage On Adsorptionmentioning
confidence: 76%
See 1 more Smart Citation
“…As there was a rise in the sorbent dosage of Fe 3 O 4 @SiO 2 -NH 2 nanoparticles, the percentage of removal increased, but the q e decreased. From this trend, it can be clearly understood that a rise in the number of active sites favors sorption [57]. From the results depicted in Figure 4b, it was observed that 2.0 g/L seems to give ample interchangeable binding sites for the removal of cadmium ions.…”
Section: Impact Of Dosage On Adsorptionmentioning
confidence: 76%
“…Magnetic composites-carbon nanotubes 31.25 [55] Iron oxide coated sewage sludge 42.40 [56] Manganese oxide-carbon nanotube 26.24 [57] Sugar beet pulp 24.3 [58] Fe 3 O 4 @APS@AA-co-CA MNPs 29.6 [59] oxMWCNT6h 13.5 [60] Granular sludge-clay 1.53 [61] 3.3.2. Adsorption Kinetics and Mechanism Figure 5 showed the adsorption kinetics for Cd(II) ions by Fe 3 O 4 @SiO 2 -NH 2 nanoparticles at 303 K. For ensuring the enhanced interpretation of the adsorption kinetic behavior of Cd(II) ions on the Fe 3 O 4 @SiO 2 -NH 2 nanoparticles, the most typical kinetic models like the pseudo-first, pseudo-second and intraparticle diffusion model, Elovich model, SCM model and Boyd Kinetic model have been well established to elucidate relationships of adsorption rate as well as the adsorption capacities [62].…”
Section: Adsorbents Q M (Mg/g) Referencesmentioning
confidence: 99%
“…Adsorption studies were performed by varying the solution pH, adsorbent dose, initial concentration, contact time, and temperature. The maximum improvement observed is a 14-fold increase in adsorption capacity for Pb (II) (Senthil Kumar et al 2011bKumar et al , 2018Prabu et al 2016Prabu et al , 2021Coelho et al 2018;Nuithitikul et al 2020;Yahya et al 2020). These chemical treatments modify CNSc surface functional groups and eliminate impurities, creating more active sites for adsorption and potentially enhancing surface area and pore volume (Nuithitikul et al 2020).…”
Section: Liquid-phase Applications Cashew Nutshells and Cashew Nutshe...mentioning
confidence: 99%
“…It is used to adjust the functional and technological properties of raw materials (stabilizing, water-and fatbinding abilities) and to improve the quality of finished products. [10][11][12] In addition, to increase water and fat binding, water and fat retention; improving the stabilization of polyphase systems using ZnO nanoparticles applied to a carboxymethylcellulose film; AgNPS, micro-and nanosized powders of various origins, modified nanocomposite (CNS-nZVI) with high adsorption capacity [13][14][15] are used. The expediency of their use is determined by a wide range of functional and technological properties, thanks to high dispersion, shape, structure, and physicochemical indicators.…”
Section: Introductionmentioning
confidence: 99%